Pengaruh Media Sosial Terhadap Pergeseran Makna Kata dalam Bahasa Indonesia (International Forum of Researchers and Lecturers, 2024)
The emergence of social media has changed people's communication patterns from formal to more informal and interactive. However, these changes also pose challenges to the stability and uniformity of Indonesian as a national language. Massive shifts in the meaning of words on social media are often not in line with the standard rules of the Big Indonesian Dictionary (KBBI). The aim of this research is to analyze the influence of social media on shifts in the meaning of words in Indonesian. This research method uses a descriptive qualitative analysis approach. Based on the results analysis, five types of changes in meaning found in the use of comments and caption features by Indonesian netizens on Instagram. The large amount of data on changes in meaning found in comments and captions on Instagram is expected to provide insight to the wider community so they can choose and sort out good and correct words for them. used in everyday life.